Comparative account of the effects of two high carbon alcohols (C5 & C6) on combustion, performance and emission characteristics of a DI diesel engine. Issue 14 (17th July 2020) - De Poures, Melvin Victor; Gopal, K.; Sathiyagnanam, A.P.; Rajesh Kumar, B.; Rana, D.; Saravanan, S.; Damodharan, D.
ABSTRACT: Pentanol and Hexanol are two excellent biofuels that could be derived from lignocellulosic biomass feedstock without disturbing food-based sources. The present study utilizes these two alcohols as blend constituents with diesel by up to 30% by vol. (designated as Pen30 and Hex30) in a DI diesel engine subject to modifications in injection timing (early and late) and intake air dilution through EGR (up to 30%). The modifications were intended to obtain an optimum performance of the engine. The combustion and performance characteristics of this engine were analyzed with reference to diesel operation. The results indicated that Pen30 blend experienced longer ignition delays, higher peaks of pressure and heat release rates (HRR) than Hex30 at all conditions of EGR. The premixed combustion phasing with the blends were more enhanced followed by numerous HRR spikes during diffusion phasing indicating better combustion. Both the blends delivered better brake thermal efficiencies but with a penalty in fuel consumption. Pen30 delivered better BTE but consumed more than Hex30. NOx emissions of the blends were of the order: Diesel > Pen30 > Hex30. Smoke densities of the blends were of the order: Diesel > Hex30 > Pen30. HC emissions of the blends were of the order: Pen30 > Hex30 > Diesel. CO emissions of the blends followed the trends of smoke emissions. Both these alcohols could be excellent partial substitutes for diesel with minor modifications to the engine subject to long-term tests on durability.